SOCIO-PSYCHOLOGICAL BASES OF FORMING SPEAKING COMPETENCE BASED ON STUDENTS’ CREATIVE THINKING - Bazarbayeva Raykhan Abdimumin qyzy (Web of Journals Publishing, 2025)
This article covers competencies and its socio-psychological foundations, which are formed on the basis of the personality of the reader and his creative thinking, such concepts as voluntary and involuntary creative abilities in achieving successful thinking, creative thinking and linguistic communication.
Keywords: sustainable development, risks, bank efficiency, ecology, environmental, social and corporate governance, ESG